2006
DOI: 10.1107/s174430910603096x
|View full text |Cite
|
Sign up to set email alerts
|

Structure ofBacillus halmapalusα-amylase crystallized with and without the substrate analogue acarbose and maltose

Abstract: PDB References: -amylase complexed with acarbose and maltose, 2gjp, r2gjpsf; uncomplexed, 2gjr, r2gjrsf.Recombinant Bacillus halmapalus -amylase (BHA) was studied in two different crystal forms. The first crystal form was obtained by crystallization of BHA at room temperature in the presence of acarbose and maltose; data were collected at cryogenic temperature to a resolution of 1.9 Å . It was found that the crystal belonged to space group P2 1 2 1 2 1 , with unit-cell parameters a = 47.0, b = 73.5, c = 151.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 12 publications
3
35
0
Order By: Relevance
“…. Acarbose was found to interact with the active site residues, which is overall in accordance with the binding mode of acarbose in other alpha‐amylase types . The AGGRESCAN program detected several areas in the amino acid sequences which tend to aggregate.…”
Section: Resultssupporting
confidence: 61%
“…. Acarbose was found to interact with the active site residues, which is overall in accordance with the binding mode of acarbose in other alpha‐amylase types . The AGGRESCAN program detected several areas in the amino acid sequences which tend to aggregate.…”
Section: Resultssupporting
confidence: 61%
“…In CGTase, an enzyme that resembles AM in the catalytic reaction but that differs in structure, the aromatic amino acid residue involved in the reaction specificity was identified to be outside the catalytic-site region (17). A second substrate binding site has also been reported in the ␣-amylase family, such as in bacteria (20,25), archaea (24), and plants (32). The decrease in k cat and the modest decrease in the observed K m toward malto-oligosaccharides were observed in the Y380A barley R ␣-amylase I, whereby position 380 is the binding site outside the catalytic region (4,28).…”
Section: Discussionmentioning
confidence: 99%
“…Sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (PAGE) (7.5% [wt/vol]) was carried out on a Bio-Rad Mini-Protein III gel apparatus (Bio-Rad Laboratories, Hercules, MA) using the Laemmli buffer system (25 …”
Section: Methodsmentioning
confidence: 99%
“…An explanation for the different outcome has been offered by Davies et al: the transglycosylation product in BHA is suggested to result from the initial formation of a covalent intermediate from acarbose and a series of subsequent successive transglycosylation events with maltose, rather than with acarbose as in BA2. 33 In addition to the oligosaccharide bound in the A-B groove, AmyB ACR contains an unmodified acarbose molecule bound to subsites A-D formed on the C domain in a groove between the N domain and the C domain (i.e., the N-C groove) (Fig. 3f).…”
Section: Structure Of the Amyb-acarbose Complexmentioning
confidence: 98%